Building trust by signaling trustworthiness in service retail. Issue 5 (5th August 2014) - Kharouf, Husni; J. Lund, Donald; Sekhon, Harjit
Abstract : Purpose: – The purpose of this paper is to investigate the role of retailer trustworthiness in driving customer trust and the subsequent impact on loyalty. The authors position trustworthiness as a mediator in the link between retail strategies and the development of trust. They model customer loyalty to the service retailer as a function of the trust created through trustworthy perceptions. Design/methodology/approach: – The authors validate their model using 420 survey responses from customers in a service retail setting. Nine research hypotheses were tested using structural equation modeling. Alternate models are estimated, and the results provide support for the theory-based trustworthiness mediation model. Findings: – Trustworthy behaviors first build trustworthiness, which then translates into customer trust and ultimately has a positive impact on both behavioral and attitudinal loyalty. Research limitations/implications: – The research highlights the importance for retailers to signal their trustworthiness to build customer trust and loyalty. Researchers should measure trustworthiness perceptions when examining customer relationships and managers should plan strategically to develop both trust and trustworthiness with their customers. Originality/value: – This study is one of the first to investigate the mediating effect of trustworthiness on customer loyalty in service settings. While past research has investigated dimensions of trustworthy behaviors, none has included a measure of trustworthiness perceptions and consumer trust in the same theoretical model. The results of the research provide important insights for both researchers and managers.